Water Quality Assessment at Ranchan Waterfall, Serian Sarawak - Nik Nurul Aizzah, Binti Nik Azme (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study was carried out at Ranchan Waterfall from November 2013 until March 2014 to assess water quality level based on National Water Quality Standard (NWQS) for Malaysia. A total of three sampling stations covering the study area were selected for water sampling and were signated as Station 1, Station 2 and Station 3. A total of 12 physico-chemical water parameters were analysed based on APHA and HACH standard method. The results obtained then were compared with NWQS. Result shows that the range for temperature during the sampling time was 23.80 to 25.30 ˚C, for turbidity was 0.32 to 3.09 NTU, 4.92 to 7.82 for pH , 4.48 to 9.30 mg/L for DO, 1.00 to 12.00 mg/L for TSS, 0.02 to 0.06 mg/L for nitrate, 0.02 to 0.12 for ammoniacal nitrogen and 0.03 to 0.20 mg/L for orthophosphate. According to NWQS (National Water Quality Standard for Malaysia) classification, the temperature was within the normal ranges, turbidity, conductivity, total suspended solid (TSS), chemical oxygen demand (COD), dissolve oxygen (DO), nitrate, orthophosphate, ammoniacal nitrogen were categorized under class I, while biological oxygen demand (BOD) came under class II and pH under class III. Overall, Ranchan waterfall is safe for recreational use.